2012
DOI: 10.1016/j.molcel.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Janus-Faced PIDD: A Sensor for DNA Damage-Induced Cell Death or Survival?

Abstract: In this issue of Molecular Cell, an activator of the PIDDosome (a complex comprising of PIDD, RAIDD, and caspase-2) is described in experiments detailing endogenous PIDDosome assembly and caspase-2 function after DNA damage in the presence of Chk1 suppression (Ando et al., 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Triptolide is an active extract from a Chinese herb Tripterygium wilfordii . Recent studies reveal that Triptolide enhances cancer cells sensitivity to chemotherapy drugs through apoptosis induction .…”
Section: Introductionmentioning
confidence: 99%
“…Triptolide is an active extract from a Chinese herb Tripterygium wilfordii . Recent studies reveal that Triptolide enhances cancer cells sensitivity to chemotherapy drugs through apoptosis induction .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PIDD-C, PIDD-CC is thought to be pro-apoptotic. A previous study revealed that PIDD-CC was upregulated in the brain after irradiation [50][51][52][53] . Similarly, our study showed that PIDD-CC was significantly increased at 3 h after irradiation, which indicates that the roles of different PIDD segments differ in cell survival and apoptosis after irradiation, and NF-κB pathway activation precedes apoptosis.…”
Section: Histological and Immunohistochemical Examination Of Brain Timentioning
confidence: 93%
“…This method aims to predict the values of the HDR assay for a given variant, which is a measure of the impact of this variant on BRCA1/2 molecular function. Because the output of the HDR assay is a continuous value, we opted for using an MLR as a modeling tool, as implemented in the python package Scikit-learn (Pedregosa et al, 2011). The LOOCV of the model was done with the same package.…”
Section: The Mlr Methodsmentioning
confidence: 99%
“…Here we have utilized the following: The confusion matrices, the accuracies per class, the overall accuracy, and the multiclass MCC (Gorodkin, 2004;Jurman, Riccadonna, & Furlanello, 2012). The multiclass MCC (Gorodkin, 2004;Jurman et al, 2012) was obtained using the implementation in the python package Scikit-learn (Pedregosa et al, 2011).…”
Section: Multiclass Performance Assessmentmentioning
confidence: 99%